Water Resource Management by Living Weir: A Case Study of Yangkom Living Weir- Pipoon District, Nakhon Si Thammarat Province - โยธารักษ์ ดำรง; รัตนคช นิพนธ์; สุดสมบูรณ์ สุดารัตน์; พิมพ์ประพันธ์ อัสมา; อยู่สกุล อรณุชา; คชรัตน์ พุธวิมล; อำลอย พนิตา; ปิยะพิสุทธิศักดิ์ ประภาพร (JOURNAL OF SOUTHERN TECHNOLOGY, 2019)
This research aims to study (1) factors leading to the cooperation in water resource management by living weir in Yangkom Living Weir- Pipoon District, Nakhon Si Thammarat, 2) collaborative model for water management by living weir in Yangkom Living Weir- Pipoon District, Nakhon Si Thammarat, 3) impacts of water management on physical, biological, political, economic and social factors and 4) problems and obstacles in water management by living weir and provide suggestions. The conceptual framework used in this present research is based on the concept of water management by the government, the concept of community based disaster risk management, the concept of water management by the community, the concept of water management by living weir, the concept of cooperative working, and the concept about impact studies. This present research is a qualitative research. Document analysis, in-depth interview, participatory and non-participant observation were employed to collect the data. The participants in this research were the villagers affected from the management of water by the living weir in Yangkom Living Weir- Pipoon District, Nakhon Si Thammarat. Those participants were chosen by purposive selection. Analytic induction and focus groups were used to analyze the collected data. The results revealed that 1) factors affecting the cooperation in water resource management by living weir consisted of four factors: (1.1) the relationship among people in the local area, (1.2) the communication among people in the local area, (1.3) the creation of community learning, and (1.4) the leader roles of local governmental officers. 2) The collaborative approach to the management of living weir found that the leader roles of local governmental officers used the communication among people in and out the local area through the creation of community learning to the water resource management by living weir. 3) The impact of water management by living weir on social life revealed that the process of creating a weir resulted in an atmosphere of participation of the villagers like in the past as the socially benevolent and happy society appeared in the area again. Political impact showed the integration of people in building the weir. The economic factor showed that the activities of the living weir resulted in a community economy. The physical factor found that the living weir area made the area seem to be abundant. The condition of the shallow wells of the villagers was significantly increased. It showed the seepage of the water that was raised on both sides, about 2 km. The living weir also helped prevent flooding and decrease the flow of water. The biological factor revealed that there was the increasing of aquatic species. The obvious evidence was the existence of 38 species of fish found in the area. Interestingly, many species of lost fish had appeared and 4) problems and obstacles of the living weir in Yangkom were (4.1) the size of the living weir, (4.2) the budget, (4.3) the conflict among the governmental officers, and (4.4) the conflict among each group of the villagers. This present research suggested that (1) it is necessary to understand governmental agencies in terms of water management concepts, (2) It is necessary to study the soil in the living weir area in order to prevent damage of the water stream, and (3) it is necessary to learn more to determine the size of the weir that can resist the water force.